2015
DOI: 10.3390/nu7115473
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Patterns and Atopic Dermatitis in Relation to GSTM1 and GSTT1 Polymorphisms in Young Children

Abstract: Previous research suggests the association of glutathione S-transferase (GST) gene polymorphisms or diet, but no interactions between these factors in atopic dermatitis (AD). We conducted a community-based case-control study including 194 AD and 244 matched non-AD preschoolers. Glutathione S-transferase M1 (GSTM1) and T1 (GSTT1) present/null genotypes were evaluated uisng a multiplex PCR method. We measured dietary intakes by a validated food frequency questionnaire and constructed three dietary patterns such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Individual dietary data for the past year were collected by the parents or guardians and validated by trained interviewers using the FFQ (90 food items). Both the reproducibility ( r value = 0.5–0.8) and validity ( r value = 0.3–0.6) of the instrument were acceptable, as reported elsewhere [ 18 , 19 ]. We used the same questionnaire at both follow-ups.…”
Section: Methodssupporting
confidence: 78%
“…Individual dietary data for the past year were collected by the parents or guardians and validated by trained interviewers using the FFQ (90 food items). Both the reproducibility ( r value = 0.5–0.8) and validity ( r value = 0.3–0.6) of the instrument were acceptable, as reported elsewhere [ 18 , 19 ]. We used the same questionnaire at both follow-ups.…”
Section: Methodssupporting
confidence: 78%
“…In a case–control study of Korean children, the GSTM1 -null genotype was significantly associated with childhood AD onset [33]. However, Chung et al found that a healthy dietary intake and the GSTM1 -present genotype had a protective effect against AD [34]. Furthermore, Carlsten et al indicated that the GSTT1 genotype enhanced the ambient diesel exhaust exposure-mediated increase in allergen-sensitized inflammation in airways among atopic participants [35].…”
Section: Discussionmentioning
confidence: 99%
“…35 A GSTM1 polymorphism has been reported to increase the potential protective role of the "Korean traditional healthy" diet against AD, and the CD14 polymorphism was also shown to influence the effect of prenatal antioxidant intake on infant respiratory infections in Korean children. 57 microbiota across different groups of infants as follows: 1) all infants whose mothers had high confectionery dietary patterns vs all infants whose mothers had low confectionery dietary patterns; 2) infants who breastfed for at least 6 months and whose mothers had high confectionery dietary patterns vs infants who breastfed for at least 6 months and whose mothers had low confectionery dietary patterns; 3) all infants who were diagnosed with FA vs all infants who were not diagnosed with FA; 4) infants who were diagnosed with FA and whose mothers had high confectionery dietary patterns vs infants who were not diagnosed with FA and whose mothers had low confectionery dietary patterns.…”
Section: Relationship Between Infant Genetic Polymorphisms and Maternalmentioning
confidence: 99%
“…However, these genetic polymorphisms are considered to be important for allergic diseases in the Korean population, as shown in our previous studies. [57][58][59][70][71][72] This study is the first to assess the relationship between infant genetic variations and maternal dietary patterns on the development of infant FA in a birth cohort. In addition, unlike other studies of dietary patterns associated with allergy development, we suggested a possible mechanism for the relationship between the maternal confectionery dietary pattern and FA, namely the lipotoxic effect of TFAs.…”
Section: The Strengths and Limitationsmentioning
confidence: 99%